To find the value of the expression \((-5)^{-3}\), we can follow the steps outlined in your question.
-
Apply the negative exponent rule: \[ (-5)^{-3} = \frac{1}{(-5)^3} \]
-
Expand the power: \[ (-5)^{-3} = \frac{1}{(-5)^3} = \frac{1}{(-5)(-5)(-5)} \]
-
Simplify: Now we need to calculate \((-5)(-5)(-5)\):
- First, calculate \((-5)(-5) = 25\).
- Then, calculate \(25 \times (-5) = -125\).
Therefore, \((-5)^3 = -125\).
Putting it back into our expression: \[ (-5)^{-3} = \frac{1}{-125} = -\frac{1}{125} \]
Now we have: \[ x = -125 \]
Thus, the correct response is:
- \(x = -125\) (x is equal to negative 125).